Bringing History to Life: Teaching Materials for the Merdeka Curriculum - Alim Septyawan; Anwar Senen (Universitas Pendidikan Ganesha, 2025)
Social studies learning in elementary schools often faces challenges because instructional materials tend to be abstract and lack relevance to students’ daily experiences. This condition reduces student engagement and results in suboptimal learning outcomes. This study aimed to analyze and develop contextual social studies teaching materials that enhance student engagement and deepen conceptual understanding at the elementary level. The research employed the ADDIE development model and involved 115 fourth-grade students, two content experts, one media expert, and one instrument expert. Data were collected through observation, interviews, and questionnaires and analyzed using both qualitative and quantitative descriptive techniques. The findings revealed that the materials were rated as highly valid by content experts (4.28 out of 5) and valid by media experts (3.83 out of 5). Student responses also indicated a very good category with an average of 3.42 out of 4. These results confirm that contextual-based teaching materials are not only valid and effective but also transformative in fostering engagement and cultural appreciation among students. The implications highlight the importance of integrating contextual approaches into the Merdeka Curriculum to provide meaningful learning experiences.